Analisis perbandingan kinerja keuangan antara perbankan syariah dan perbankan konvensional pada periode Maret 2007 sampai Maret 2009 - ABADI, Yusanto Trisno ([Yogyakarta] : Universitas Gadjah Mada, 2010)
In this research had been compared between Islamic with conventional banks in Indonesia in terms of: CAR ratio; return on assets (ROA) return on equity (ROE); correlation CAR ratio with return on equity (ROE), and correlation the amount of deposits with return on assets and return on equity, which are possible to have differences. Published quarterly financial statements for the period March 2007 to March 2009 from three Islamic banks and nine conventional banks (listed in Indonesia Stock Exchange) will be analyzed to test the six hypotheses that have been made. Statistical analysis performed using t and Pearson correlation tests. As we are understood that the return on debt in the conventional banks based on the interest rate so that the debt has properties rigidity. Meanwhile, in the Islamic bank, debt repayment is based on profit and loss-sharing scheme. These results obtained, in the period March 2007 to March 2009, conventional banks have CAR ratio higher than Islamic banks. Thus, conventional banks have the ability to better capital to cover possible losses from the various risks faced in operations compared with Islamic banks. In Roe, there is a difference between Islamic banks and conventional banks. In this variable, Islamic banks have better capabilities than the conventional banks in managing investor funds to generate profits. Meanwhile, there is no significant difference between the ROA Islamic banks with conventional banks. Furthermore, there is no difference between the correlation coefficient of CAR ratio with ROE in Islamic and conventional banks. However, there are differences in the correlation coefficient between the number of third party funds (deposit account) with ROA and ROE in Islamic and conventional banks. In this case, the correlation coefficient between the number of third party funds with ROA and ROE in the conventional banks is stronger than in the Islamic bank. Finally, this research opens new study about the relationship between depositors and shareholders, especially in Islamic bank, though additional research is required on this aspect.